O ensino de Botânica de angiospermas: classificação e diferenciação dos frutos em uma escola pública no município de Humaitá-Am - Calisto, Jeiciana Gomes (Brasil, 2024)
Botany teaching specifically about Angiosperms, which is the largest group of plants in the world, characterized by the presence of flowers, fruits and seeds, still follows a traditional methodology, where classes are focused only on the textbook. Through this, the respective project aimed to contribute to the students' understanding of angiosperms, specifically about the fruits, in which these students could acquire knowledge to verify the classification and the main characteristics of the fruits present in their daily lives, when are requested. The work started from a bibliographical research, giving us theoretical basis for the elaboration and application of the search. The methodology consisted of a preliminary survey by questionnaire with subjective questions, expository class on the fruits and concluded with a practical class that consisted of the preparation of a fruit salad, and during the preparation the students brought the classification and characteristics of the fruits according to your learning. The previous survey was obtained through the pre-questionnaire where they answered according to the knowledge they already had about the fruits. In view of the answers, we performed the practical class on the subject and approached it with the purpose of verifying the students' performance in se, and for that it was necessary to compare before and after this practical class analyzing the answers of the pre and post-questionnaire, with this we verified how useful it was, thus contributing to the knowledge of each one, so that they associate the knowledge acquired with their day to day, since it is something so present in everyday life.